Cylindrical excavations in clayey soils retained by jet grout walls: Numerical analysis and parametric study considering the influence of consolidation - José Leitão Borges (2014)
Using a computer program based on the finite element method, a study is conducted to analyse the consolidation-dependentbehaviour of a cylindrical excavation in a clayey soil, retained by a jet-grout wall. Aparametric study is also performed in order to analyse the influence of three factors, namely the diameterof excavation, the embedded length of the wall and the elastic modulus of the wall material. The numericalmodel incorporates the Biots consolidation theory (coupled formulation of the equilibrium and flowequations) with soil constitutive relations simulated by the pqh critical state model. Special emphasisis given to the analysis of excess pore pressures and displacements in the ground, as well as circumferentialcompression stresses, bending moments and horizontal displacements in the wall, and earth pressureson the wall faces.